Investigation of the in vitro regeneration of mericlones in the caribe variety of carnation - Kiss, Zs. O.; Balogh, A.; Fodorpataki, L. (International Journal of Horticultural Science, 2001)
In vitro culture conditions were experimented for the relatively sensitive, but very esthaetic "Caribe" variety of carnation with uniformly dark violet flowers. Regeneration of new plants from shoot apex meristems can be significantly improved by the combined addition of very low amounts of indolebutiric acid, benzyladenine and gibberelic acid, dissolved in the Murashige-Skoog nutrient medium. Callus formation as a prerequisite for the induction of somaclonal variability can be achieved successfully with certain molar ratios between 2,4-dichlorophenoxyacetic acid and benzyladenine. Acclimation of the obtained mericlones to the ex vitro conditions was also evaluated.